Rancangan Sistem Informasi Penjualan Furniture pada Toko Mebel Pondok Baru Berbasis Web - Wahid Wijaya; Muhammad Sulthon Abdillah; Tinuk Agustin (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Pondok Baru Furniture Store located in Makamhaji Kartasura is a business that operates in the field of manufacturing and selling furniture. There are problems in managing sales transaction data, stock of goods, and sales reports which still use manual methods, sometimes resulting in errors in recording. The current purchasing system which requires coming to the shop to see and buy the products being sold is very troublesome. And consumers want to know about the products being sold without having to come to the shop directly. Therefore, researchers created a web-based sales information system to overcome this problem. The method used in system development is the prototype method with data collection through interviews. The result is a web sales information system design that makes it easier for buyers to access products offered anywhere and carry out purchase transactions online. This system design is expected to produce more accurate data in processing sales data and sales reports.